2009
DOI: 10.1089/ten.tea.2009.0235
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid—An Alternative to Aprotinin in Fibrin-Based Cardiovascular Tissue Engineering

Abstract: Recent clinical trials have led to the worldwide suspension of aprotinin, the most commonly used antifibrinolytic agent in fibrin-based tissue engineering. For future clinical applications of fibrin-based scaffolds, a suitable, alternative fibrinolysis inhibitor must be identified. The present study aimed to evaluate tranexamic acid (trans-4-aminomethyl-cyclohexane-1-carboxylic acid [t-AMCA]) as an alternative fibrinolysis inhibitor to aprotinin for cardiovascular tissue engineering applications. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 39 publications
1
55
0
1
Order By: Relevance
“…• Fibrin gel is a naturally-occurring scaffold that can be isolated as an autologous substrate from blood of the patient in question (Heselhaus, 2011); • Starting with a cell suspension in fibrinogen solution, fibrin gel scaffolds offer immediate high cell seeding efficiency and homogenous cell distribution by gelation entrapment, with a minimal loss of cells during the seeding procedure; furthermore, there is no time-consuming cell ingrowth from the scaffold surface to the deeper parts of the scaffold (Jockenhoevel et al, 2001a); • Polymerisation as well as degradation of the fibrin gel is controllable and can be adapted to tissue development through the use of the protease inhibitors, such as aprotinin and tranexamic acid (Cholewinski et al, 2009); • Local, covalent immobilisation of different growth factors is possible, while PRP gels can be developed to enhance the content and delivery of growth factors (Wirz et al, 2011); • Production of complex 3-D structures such as heart valve conduits or vascular grafts with complex side branches is possible through the use of an injection moulding technique (Flanagan et al, 2007;Jockenhoevel et al, 2001b); • Textile-reinforced fibrin-based grafts can be implanted in the arterial circulation and function for at least 6 months in vivo (Koch et al, 2010); • Fibrin-based tissue engineering can be merged with self-expanding stents to create a platform technology for cardiovascular, and other, diseases. These properties highlight the significant potential for creation of functional, autologous implantable cardiovascular prostheses in future using tissues derived from the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Fibrin gel is a naturally-occurring scaffold that can be isolated as an autologous substrate from blood of the patient in question (Heselhaus, 2011); • Starting with a cell suspension in fibrinogen solution, fibrin gel scaffolds offer immediate high cell seeding efficiency and homogenous cell distribution by gelation entrapment, with a minimal loss of cells during the seeding procedure; furthermore, there is no time-consuming cell ingrowth from the scaffold surface to the deeper parts of the scaffold (Jockenhoevel et al, 2001a); • Polymerisation as well as degradation of the fibrin gel is controllable and can be adapted to tissue development through the use of the protease inhibitors, such as aprotinin and tranexamic acid (Cholewinski et al, 2009); • Local, covalent immobilisation of different growth factors is possible, while PRP gels can be developed to enhance the content and delivery of growth factors (Wirz et al, 2011); • Production of complex 3-D structures such as heart valve conduits or vascular grafts with complex side branches is possible through the use of an injection moulding technique (Flanagan et al, 2007;Jockenhoevel et al, 2001b); • Textile-reinforced fibrin-based grafts can be implanted in the arterial circulation and function for at least 6 months in vivo (Koch et al, 2010); • Fibrin-based tissue engineering can be merged with self-expanding stents to create a platform technology for cardiovascular, and other, diseases. These properties highlight the significant potential for creation of functional, autologous implantable cardiovascular prostheses in future using tissues derived from the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid is clinically approved and competitively inhibits the conversion of plasminogen into plasmin via reversibly binding to the lysine-binding site on plasminogen. Cholewinski et al (2009) demonstrated that tranexamic acid at a concentration of 160 mg per mL medium has a comparable inhibition effect on fibrinolysis in comparison with aprotinin. Furthermore, no negative side-effects with regard to proliferation, apoptosis, necrosis or the burst strength of the produced fibrin gel scaffolds could be demonstrated (Cholewinski et al, 2009).…”
Section: Control Of Scaffold Degradation (Aprotinin Vs Tranexamic Acid)mentioning
confidence: 96%
“…After three additional days, dermal and fullthickness skin grafts were exposed to air contact, by lowering culture media levels. In addition, total Ca 2 + concentration was increased to 1.2 mM for the airlift culture and all media were supplemented with 0.1% Gentamicin, 0.16 mg/mL tranexamic acid (Cyklokapron Ò ; Pfizer, Inc., New York, NY) 13 , and 0.5 mM vitamin C (Sigma-Aldrich). Culture medium was exchanged once per week with daily medium level controls and adjustments were made, if deemed necessary.…”
Section: Skin Graft Preparationmentioning
confidence: 99%
“…Normally, in the fibrin gel culture medium, a chemical like aprotinin is used to inhibit fibrinolysis. However, it is possibly toxic to the cells [35]. Without aprotinin, a high degradation rate results in a rapid loss of the supporting matrix before the maturation of the delivered cells and the establishment of angiogenesis.…”
Section: Matrigelmentioning
confidence: 99%